Politeness Strategies of The Panders in Women Trafficking - Ike Revita; R. Trioclarise; Nilla Anggreiny (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2017)
AbstractWomen trafficking is a kind of activity in which women are exploited. In women trafficking activity , there is no consideration of women’s right. The target is those women can be used to get money as much as possible. The women can become the victim of women trafficking is due to the ability of the panders in doing persuasion. Through various strategies, these panders are successful in pushing these women to fall into this inhuman activity. One of the strategy is by politely ensuring them. This writing is aimed at describing the politeness strategy used by panders in persuading women to be the victim of women trafficking. The research is conducted in West Java (Bekasi, Cirebon, and Indramayu). The data are any utterances of the panders in persuading the women to be the victim of women trafficking. Observational method with note-taking, recording, and interviewing is used to collect data. The analysis is done by pragmatic and referential identity method related to the concept of politeness proposed Brown and Levinson (1987), Oktavianus and Revita (2013), Leech (2014), and Mira (2010). The result of analysis is descriptively presented. Having analyzed data, it is found that there are four politeness strategies used by the panders in woman trafficking activities. They are ( (a) bald on record; (b) positive politeness; (c) negative politeness; and (d) off record.—AbstrakPerdagangan perempuan merupakan bentuk kegiatan ekploitasi perempuan. Di sini, perempuan dijadikan sebagai ajang komoditas. Tujuannya adalah utk menjadikan perempuan sebagai alat pencari uang sebanyak2nya. Perempuan sdh banyak yg jadi korban praktik perdagangan perempuan paracalo nakal. Mereka (Paracalo) ini berhasil menjerat para perempuan dg menggunakan berbagai strategi. Salah satu strateginya adalah dg cara meyakinkan/membujuk sikorban. Tulisan ini bertujuan utk memaparkan strategi paracalo dlm menjerat korbannya. Penelitian ini dilakukan di wilayah Jawa Barat (Bekasi, Cirebon, and Indramayu). Data penelitian ini diambil dari keterangan paracalo perdagangan perempuan. Pengumpulan data dilakukan melalui metode observasi dg mencatat, merekam, dan melakukan wawancara. Teknik analisi yg digunakan adlh analisis pragmatik dan metode identitas referensi yg relevan dg konsep “kesopanan” yg diusung olh Brown and Levinson (1987), Oktavianus and Revita (2013), Leech (2014), and Mira (2010). Data yg sdh terkumpul dianalisis secara deskriptif. Berdasarkan hasil analisis, penelitian ini menyimpulkan ada empat macam strategi kesopanan yg digunakan olh paracalo dlm mendekati mangsanya: (a) bald on record; (b) positive politeness; (c) negative politeness; and (d) off record. Kata kunci: strategi kesopanan, perdagangan perempuan, korban, calo, perempuan.DOI: 10.15408/al-turas.v23i1.4810